Serat Tanaman Mendong Sebagai Fiber Jacket Untuk Perkuatan Kolom Beton Bertulang Pasca Kerusakan Bangunan - Dwi Sulistiyawati; Noor Mohammad Hatta; Fariz Wahyu Setiawan; Arny Wasis Enggarriny; Agustinus Sungsang Nana Patria (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Column collapse can be overcome by increasing the nominal strength of the cross section, one of which is by strengthening using FRP (Fiber Reinforced Polymer). This research will focus on the effect of using mendong plant fiber as a fiber jacket for strengthening reinforced concrete columns after building damage. Starting from material testing, mix design calculations, making test objects and testing test objects. There are 3 variations of test objects, namely concrete without a layer of Mendong fiber, concrete with 2 layers of Mendong fiber and concrete with 4 layers of Mendong fiber. The number of test objects was 15 concrete cylinders and 6 reinforced concrete columns. Reinforced concrete column specimens were subjected to axial testing to obtain the maximum axial load. Based on the test results, it was found that the average axial strength of reinforced concrete columns without mendong fiber blanket was 120.03 kN, the average axial strength of post-damaged reinforced concrete columns with 2 layers of mendong fiber blanket was 134.46 kN and the average axial strength of post-damaged reinforced concrete columns damaged with a 4-layer mendong fiber blanket of 144.83 kN. The greater the number of layers of mendong fiber, the axial strength of the post-damaged reinforced concrete column will increase with an increase of 12.02% for 0 layers to 2 layers, and 7.71% for 2 layers to 4 layers. Based on the results of this research, mendong fiber can be used as an alternative to fiber jacket for reinforcing reinforced concrete columns after building damage.